2016
DOI: 10.1039/c6cc06262h
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed dearomative arylalkynylation of indoles

Abstract: A palladium-catalyzed indole dearomative bisfunctionalization via a domino arylation/alkynylation sequence has been developed, which provides a reliable approach to a series of structurally diverse tetracyclic indolines bearing vicinal tertiary and quaternary stereocenters in moderate to good yields and excellent diastereoselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…1a) [10][11][12][13][14][15][16] . On the other hand, as disclosed recently by the groups of Lautens [17][18][19][20] , Liang 21 , Yin 22,23 , Zhou 24 , Wu 25 , and us [26][27][28][29][30] , the application of endocyclic C=C bonds of heteroarenes as non-classic olefins has enabled a number of efficient dearomative difunctionalization reactions of indoles and furans with Pd-or Ni-catalyst 31 . This dearomatizing strategy undoubtedly expands the scope of olefin difunctionalization reaction to arenes and constitutes an important method for the synthesis of valuable three-dimensional molecules from simple planar aromatics [32][33][34][35][36][37][38] .…”
mentioning
confidence: 99%
“…1a) [10][11][12][13][14][15][16] . On the other hand, as disclosed recently by the groups of Lautens [17][18][19][20] , Liang 21 , Yin 22,23 , Zhou 24 , Wu 25 , and us [26][27][28][29][30] , the application of endocyclic C=C bonds of heteroarenes as non-classic olefins has enabled a number of efficient dearomative difunctionalization reactions of indoles and furans with Pd-or Ni-catalyst 31 . This dearomatizing strategy undoubtedly expands the scope of olefin difunctionalization reaction to arenes and constitutes an important method for the synthesis of valuable three-dimensional molecules from simple planar aromatics [32][33][34][35][36][37][38] .…”
mentioning
confidence: 99%
“…[9] Further,t hrough aH eck/benzyl-Pd capture sequence,d iastereoselective indole dearomative difunctionalization reactions were established, as reported by the groups of Lautens and Liang, as well as ourselves.This sequqnce furnishes ar ange of 2,3-disubstituted indolines, bearing vicinal stereocenters,b ya rylcyanation, diarylation, and arylalkynylation reactions. [10] Nevertheless,enantioselective dearomative Heck arylation of indoles remains underexploited, [9b, c] and so far no example has been reported for the asymmetric dearomative difunctionalization reaction. Herein, we describe ap alladium-catalyzed dearomative arylalkynylation of indoles proceeding by aH eck/Sonogashira sequence using an ew BINOL-based phosphoramidite as the chiral ligand (Scheme 1b).…”
mentioning
confidence: 99%
“…Slightly lower enantioselectivities were observed when [Pd(dba) 2 ]w as replaced by either Pd(CH 3 CN) 2 Cl 2 or Pd(OAc) 2 (entries 3a nd 4). Subsequent ligand examination revealed that the amino substituent of BINOL-based phosphoramidite ligands significantly influenced the enantioselectivity (entries [5][6][7][8][9][10][11][12][13][14]. Increasing the size of the amino substituent could improve the enantioselectivity.T he diisopropyl amino ligand L3 led to 84 %y ield and 62 % ee,w hile relatively lower ee values were achieved for L2 and L4, bearing benzyl and n-butyl substituents,r espectively (entries 5-7).…”
mentioning
confidence: 99%
“…[8] Based on dearomative Heck and reductive Heck reactions,f acile construction of C2-substituted indolines,b earing as ingle stereocenter,has been realized by Yao, Wu et al,Fukuyama et al,a nd ourselves. [10] Nevertheless,enantioselective dearomative Heck arylation of indoles remains underexploited, [9b, c] and so far no example has been reported for the asymmetric dearomative difunctionalization reaction. [10] Nevertheless,enantioselective dearomative Heck arylation of indoles remains underexploited, [9b, c] and so far no example has been reported for the asymmetric dearomative difunctionalization reaction.…”
mentioning
confidence: 99%
“…Subsequent ligand examination revealed that the amino substituent of BINOL-based phosphoramidite ligands significantly influenced the enantioselectivity (entries [5][6][7][8][9][10][11][12][13][14]. Surprisingly,t he addition of CuI (5 mol %) as ac o-catalyst fully suppressed the reaction (entry 2).…”
mentioning
confidence: 99%